2002
DOI: 10.1055/s-2002-23554
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis Gravidarum Is Associated with Oxidative Stress

Abstract: Hyperemesis gravidarum (HEG), associated with pregnancy, is a severe form of nausea and vomiting causing decrease in nutrient antioxidants. Hence, we hypothesize that oxidation injury may be involved in the pathogenesis of HEG. Plasma levels of the ubiquitous antioxidant, reduced glutathione (GSH) may serve as a sensitive measure for systemic oxidative stress. Women with pregnancies complicated by HEG (study group) were compared with pregnant women without HEG (pregnant control group) and with healthy nonpregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…During normal pregnancy, leukocyte activation produces an inflammatory response, which is associated with increased production of SO anions in the 1 st trimester [64,65]. Importantly, OS during the 2 nd trimester of pregnancy is considered a normal occurrence, and is supported by mitochondrial production of lipid peroxides, free radicals, and vitamin E in the placenta that increases as gestation progresses [66-69].…”
Section: Oxidative Stress In Female Reproductionmentioning
confidence: 99%
“…During normal pregnancy, leukocyte activation produces an inflammatory response, which is associated with increased production of SO anions in the 1 st trimester [64,65]. Importantly, OS during the 2 nd trimester of pregnancy is considered a normal occurrence, and is supported by mitochondrial production of lipid peroxides, free radicals, and vitamin E in the placenta that increases as gestation progresses [66-69].…”
Section: Oxidative Stress In Female Reproductionmentioning
confidence: 99%
“…However, as indicated previously, free radical generation under controlled conditions plays an important role in cellular homeostasis. Increased oxidant formation and even the presence of oxidative stress is considered normal during the second trimester of pregnancy (16,17). Elevated generation of free radicals by placental mitochondria has been reported in pregnancy (18).…”
Section: Free Radicalsmentioning
confidence: 99%
“…Fait et al 10 found plasma GSH levels were significantly lower in pregnant women with HG compared with healthy pregnant women. GSH is the most abundant functional thiol compound presenting in the intracellular milieu.…”
Section: Discussionmentioning
confidence: 97%
“…There is some evidence of the relationship between HG and oxidative stress. 10 First, the decreased nutritional intake is observed in patients with HG. As a result of insufficiency of dietary intake of vitamins, such as vitamin C and E and other energy sources and enhanced demands, imbalance occurs.…”
Section: Introductionmentioning
confidence: 99%